2011
DOI: 10.1245/s10434-011-2144-y
|View full text |Cite
|
Sign up to set email alerts
|

Right Paraesophageal Lymph Node Dissection in Papillary Thyroid Carcinoma

Abstract: RPELN dissection should be considered in patients with right thyroid cancer, tumors larger than 1 cm, or multiple CLN metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 27 publications
3
35
2
Order By: Relevance
“…This may be because of some limitations in our sample selection, in that we excluded patients with tumors only involved in the left lobe. Notably, Kim and Park 19 found that right paraesophageal lymph nodes could be the solely metastatic region from PTC, which was supported by the evidence from both our study (6.4%; 26 of 405) and Bae et al 18 Of interest, Kim and Park 19 also observed that 1 of the patients with PRRLN positivity had a tumor only in the left thyroid lobe, which thus indicated the necessity for routine detection of right paraesophageal lymph nodes during PTC surgery regardless of whether tumors were located in the right or left lobe. According to the review by Weber and Holsinger, 21 for a PTC tumor arising in 1 lobe of the thyroid, tumor emboli may traverse the subcapsular lymph nodes and consequently produce metastatic deposits in the contralateral lobe.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may be because of some limitations in our sample selection, in that we excluded patients with tumors only involved in the left lobe. Notably, Kim and Park 19 found that right paraesophageal lymph nodes could be the solely metastatic region from PTC, which was supported by the evidence from both our study (6.4%; 26 of 405) and Bae et al 18 Of interest, Kim and Park 19 also observed that 1 of the patients with PRRLN positivity had a tumor only in the left thyroid lobe, which thus indicated the necessity for routine detection of right paraesophageal lymph nodes during PTC surgery regardless of whether tumors were located in the right or left lobe. According to the review by Weber and Holsinger, 21 for a PTC tumor arising in 1 lobe of the thyroid, tumor emboli may traverse the subcapsular lymph nodes and consequently produce metastatic deposits in the contralateral lobe.…”
Section: Discussionsupporting
confidence: 88%
“…Very few other studies have produced data on associations with lymph node PRRLN positivity in patients with PTC. To our knowledge, so far, there are only 4 related reports (Table ) with the lymph nodes deep to the right RLN called “right paraesophageal lymph nodes.” Unlike our study, Bae et al and Kim and Park defined right paraesophageal lymph nodes as an isolated region from the central compartment. The frequency of lymph node PRRLN positivity in our patient population was a little higher than the 4 previous studies.…”
Section: Discussioncontrasting
confidence: 60%
“…The left and right RLNs have slight differences in anatomical position, and the cervical part of the esophagus located closely next to the left. Therefore, there was a triangular space located posterior to the right RLN, which makes space for lymph adipose tissue [15][16][17] . In the literatures, the presence of Hashimoto's thyroiditis leads to reactive lymphaden proliferation 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the same issue for pre-and right paratracheal to this region is very difficult. To date, few studies have been published regarding this issue [5][6][7] and only two demonstrated any statistical data for these nodes [6,7]. However, the number of patient employed in their studies is small, and they analyzed patients with various N factors [8] in a single group.…”
mentioning
confidence: 99%
“…However, the number of patient employed in their studies is small, and they analyzed patients with various N factors [8] in a single group. One study performed multivariate logistic analysis, but they analyzed pre-, intra-, and postoperative factors at the same time [7].…”
mentioning
confidence: 99%